MODEL PEMBERDAYAANMASYARAKAT DENGAN PENDEKATAN SOCIAL ENTREPRENEURSHIP: Analisis Ketokohan Para Pewirausaha Sosial - Masturin Masturin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
The first purpose of this article is to defineabout a social empowerment model through social entrepreneurship. Furthermore, social entrepreneurship figures are also analyzed as a second purpose to support the concept of the implementation. Social entrepreneurship is one of social empowerment models to solve social problems and to create social change using entrepreneurial principles. The characteristics of the model are to create social value, social entrepreneur, social entrepreneurship organization, market orientation, and social innovation. The figures who accomplished in executing the model such as the founder of Grameen Bank, the leader of Islamic Boarding School Al-Ittifaq in Bandung, and the leader of Islamic Entrepreneurial School Abdurahman bin Auf in Klaten.